Gastroprotective Effect of Samudradya Churna wsr of Parinama Shula: A Classical Review (AYUSHDHARA, 2023)
According to several researches on the number of cases of duodenal ulcers, these conditions are believed to affect 5 to 15% of the general population. While dyspepsia is among the most common accompanying symptom of duodenal ulcers, the presentation can range in severity, including gastrointestinal bleeding, gastric outlet obstruction, perforation, or fistula development. This whole entity compared as Parinama Shoola is an Avaranjanya Tridoshaja Vyadhi caused by Vata vitiation, which causes avarana in Kapha and Pitta. It worsens during meal digestion and 3-4 hours after food intake when it gets to the intestines. In modern science, there are drugs for symptomatic relief in the treatment of ulcers (Parinama Shula) that have severe adverse consequences over time. In the Current era, there is a critical need to protect the microbiota of the gut as well as digestive health through the use of Ayurvedic formulations both for preventive and therapeutic purposes. Finally, it is discussed the use of one of the Ayurveda Formulation “Samudradya Churna” with respect to its role in health and disease. This article reviews the indications, contraindications, pharmaceutical action, adverse events, and other key elements in the clinical setting as relates to the essential points.